Social support for parents of premature infants - Skurzak, Agnieszka; Iwanowicz-Palus, Grażyna Jolanta; Korżyńska-Piętas, Magdalena; Kicia, Mariola; Żółkiewska, Beata (Journal of Education, Health and Sport, 2018)
Prematurity is still an actual medical problem. Significant increase in the survival rate of premature babies is observed due to the progress in perinatal care .Usually, parents are not prepared for a premature birth, for the majority of them the hospitalization of a child in neonatal intensive care unit is a source of fear, moreover parents often blame themselves for the situation. Appearing emotions and questions require a compatible response from the therapeutic team. The most important activity in the practice of the team is emotional, informative, evaluative support.